STRATEGI PEMBELAJARAN DARING DI DINAS PENDIDIKAN KOTA MAKASSAR - Alamsyah, Habibie; Mappamiring, Mappamiring; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2022)
ABSTRACT This study aimed to find out the establishment, implementation and evaluation of online learning at the Makassar City Education Office. This study used the Mix Method. The informants of this study were eight people with data collection techniques used interviews, observations and documentation. Data analysis were data reduction, data presentation, data verification and conclusion making. The results of the study showed some aspects of online learning strategy were (a) Determination was to determine between online or offline learning process and making RPP in accordance with the circular issued by the government regarding online learning. (b) Implementation, the agency gave full rights in the application of the online learning process, as well as providing facilities to teachers who did not understand technology and also gave an understanding of what systems were used during learning. It was support learning to be more effective and efficient. (c) Evaluation, in this online learning for the achievement of evaluation in the K13 curriculum the average was 70-75% and it was still not maximal in the accumulation of teacher assessments of their students. And the teacher's evaluation was in the form of giving assignments to students which became the accumulation of additional values. Keywords: Strategy, Online learning